(untitled) (Brazilian Journal of Pharmaceutical Sciences, 2020)
The membrane-based efflux pump systems are recognized to have an important role in pathogenicity and drug resistance in Mycobacterium tuberculosis by the extrusion of toxic substrates and drugs from the inner bacillus. This study aimed to investigate the in vitro interaction of Verapamil (VP), an efflux pump inhibitor, with the classical first-line anti-tuberculosis drug isoniazid (INH) in resistant and susceptible M. tuberculosis clinical isolates. Seven multidrug-resistant (MDR), three INH monoresistant and four susceptible M. tuberculosis clinical isolates were tested for the INH and VP combination by modified Resazurin Microtiter Assay Plate (REMA). Fractional Inhibitory Concentration (FIC) and Modulation Factor (MF) were determined. The INH plus VP combination showed no significant change in the Minimum inhibitory concentration (MIC) values of INH (FIC≥ 0.5; MF=1 or 2).The use of VP in tuberculosis therapy should be managed carefully, considering the resistance caused by specific mutation in katG and inhA genes, in which the use of these EPIs may have no success. The use of EPIs as an adjunctive drug in the anti-tuberculosis therapy should be further investigated on a larger number of M. tuberculosis clinical isolates with different resistant profile.